2009
DOI: 10.1002/pen.21341
|View full text |Cite
|
Sign up to set email alerts
|

Studies on fluorescent PVA + PVP + MPDMAPP composite films

Abstract: Polymer blends along with 1-(4-methylphenyl)-3-(4-N,N, dimethyl amino phenyl)-2-propen-1-one (MPDMAPP) NLO-chromophore-doped composite films were prepared by solvent casting method using DMF. The optical properties were studied using UV-visible, refractive index, steady state fluorescence, and fluorescence microscopic imaging techniques. The UV-vis absorption spectra showed three absorption bands and were assigned to localized n ? p*, n ? p* inter band, and p ? p* transition of charge transfer groups. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…In this context, the blending of poly(vinyl alcohol) (PVA) and poly(vinyl pyrrolidone) (PVP) leads to a water-soluble and biodegradable polymer with improved mechanical properties. [6][7][8] Sericin is a natural, macromolecular water-soluble protein derived from silk cocoons. The silk fibers are composed of a protein fibroin with sericin surrounding it, and the removal of sericin from silk fiber is accomplished by a process called degumming.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the blending of poly(vinyl alcohol) (PVA) and poly(vinyl pyrrolidone) (PVP) leads to a water-soluble and biodegradable polymer with improved mechanical properties. [6][7][8] Sericin is a natural, macromolecular water-soluble protein derived from silk cocoons. The silk fibers are composed of a protein fibroin with sericin surrounding it, and the removal of sericin from silk fiber is accomplished by a process called degumming.…”
Section: Introductionmentioning
confidence: 99%
“…A few new peaks in the range 426–495 have appeared for different concentrations. These changes may be attributed to the hydrogen bonding between OH groups of PVA with different groups of PDAP and formation of CTC [ 20] as seen in FTIR results. The formation of CTC results in the creation of new molecular dipoles or reorientation of the already existing dipoles.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the molecules having π‐bonds, upon excitation with polarized light, undergo successive isomerization and change their orientation. Hence, the increase in fluorescence intensity may be thought to be due to dipole–dipole interactions because of aggregation of chromophores as with the case of chalcone‐doped PVA [20]. And also the observed stokes‐shifted emission is due to different extents of stabilization of the photo generated charge species in the excited state.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier article, we have reported PALS results of MPDMAPP chalcone chromophore doped PVA and showed that the formation of CTCs alter the microstructural properties of PVA . In another article, we have also reported about the photochromic nature in fluorescence emission properties of MPDMAPP doped PVA/PVP blend due to intermolecular hydrogen bonding and formation of CTCs. The UV–Vis absorption spectroscopy is an important tool to study the optical transitions and to obtain information about the optical band gap in polymeric materials.…”
Section: Introductionmentioning
confidence: 93%
“…The chalcone derivatives are noticeable materials for their excellent blue light transmittance. Polymers embedded with chalcone derivatives normally show good optical properties, fluorescence polarization, color change, fluorescent complex formation, and photochromism …”
Section: Introductionmentioning
confidence: 99%